Revisiting Globalization From a Borderless to a Gated Globe (International Perspectives on Social Policy, Administration, and Practice,, 2018)
This provocative volume takes an international, multidisciplinary approach to understanding globalization and assessing its economic, social, and environmental effects. Representing the Global North and South, it addresses important debates stemming from recent political events in the U.S. and U.K., the continuing rise of information technology, and the constant struggle between corporate interests and the health of the planet.The human outcomes of world human rights challenges are considered in the ongoing global narratives of migrants, refugees, and disabled persons, as well as possibilities for greater social equity and integration.This expert synthesis takes critical steps to reshape the concept of globalization from an amorphous mass of objectives and initiatives to a forward-looking model of clarity and balance. Included in the coverage: Globalization and migration: is there a borderless world A comparative assessment of climate policies of top emitters. Neo-protectionism in the age of Brexit and Trump. Working inclusively and redefining social valorization in the globalized world. Understanding the strategy of M&As in the globalized perspective. Reappraisal of social enterprise in a globalized world. Revisiting Globalism will be of particular interest to those in the academic field and the statutory and nonprofit sectors whose work deals with teaching social sciences in higher education settings. "Globalization continues to be a controversial issue. Recently we have witnessed some of the most developed countries in the world both advocating globalisation and its benefits and also advocating retrenchment and increasing isolationism. This book takes a critical perspective and examines the issue from a variety of perspectives and locations. An essential read for anyone interested in this issue." Professor David Crowther, De Montfort University, UK & Chair, Social Responsibility Research Network .